A Survey on AI-Driven Strategies and Solutions for Environmental Conservation - Ayuba Kaluri; Jalo Enoch; Mayi Magdalene (Journal of Energy Technology and Environment, 2025)
The study examines A Survey on AI-Driven Strategies and Solutions for Environmental Conservation: Insights from Conservation Professionals. The study focused on professionals and organizations working in environmental conservation and AI which includes World Wildlife Fund, Environmental Defence Fund, Ministry of Environment, National Environmental standards and Regulations Enforcement Agency, National Centre for Energy and Environmental, Nigerian Institute for Oceanography and Marine Research. A random sampling method was used for the selection of the respondents. The sample size were 200 respondents. Structured questionnaire was used for the collection of data. Descriptive statistics of mean and standard deviation was used to answer the research questions while the Inferential Statistics of Chi-square was used to test the hypotheses at 0.05 level of significance. The results revealed that, AI-driven strategies significantly improve the effectiveness of environmental conservation efforts in addressing issues like deforestation and wildlife preservation and AI-driven solutions significantly perceived to have a positive impact on the sustainability and future success of long-term conservation goals. The researcher recommended that: Conservation organizations and government agencies should allocate more funds and resources to support the adoption and development of AI technologies developing technical skills among conservation professionals is crucial for maximizing the potential of AI-driven strategies. Specialized training programs, workshops, and partnerships with technology institutions that can build the expertise required to implement and manage AI applications effectively in conservation, establishing data-sharing platforms that can enhance collaboration and knowledge exchange within the conservation community.
Nil
Keywords: AI; AI-Driven; Environmental Conservation; AI-Strategies and Solutions